Biomass-derived hierarchically porous carbon skeletons with in situ decorated IrCo nanoparticles as high-performance cathode catalysts for Li–O2 batteries. Issue 17 (10th April 2019) - Shen, Junrong; Wu, Haitao; Sun, Wang; Wu, Qibing; Zhen, Shuying; Wang, Zhenhua; Sun, Kening
Abstract : Green biomass derived three-dimensional interconnected porous carbon skeletons with in situ decorated IrCo nanoparticles were fabricated for high-performance Li–O2 batteries. Abstract : Development of an efficient air cathode with robust porous architecture and high catalytic activity toward both oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) is extremely important for lithium–oxygen (Li–O2 ) batteries (LOBs). Herein, a facile fabrication of a hierarchically porous carbon skeleton (HPCS), derived from renewable biomass precursor, as a novel cathodic material for non-aqueous LOBs is reported. The HPCS contains substantially cross-linked micro-, meso-, and macroporous channels, which can promote electron transfer, electrolyte infiltration, and oxygen diffusion, and also offers adequate room to store insoluble discharge products. The LOB developed using this rationally designed cathode material delivers a large capacity of 18 114 mA h g −1 with a high discharge plateau of 2.80 V at 100 mA g −1, which is much higher than that of commercial Super P. More importantly, HPCS can also act as a desirable matrix for other high-efficiency catalytic materials. For example, HPCS with in situ decorated IrCo nanoparticles (IrCo@HPCS) presents impressive ORR and OER catalytic performance in aqueous as well as non-aqueous media. IrCo@HPCS composite-based LOBs show a notably reduced discharge/charge overpotential, improved rate capability, and significantly enhanced stability over 200 cycles at 200 mA g −1 with the capacity limitation of 1000 mA h g −1 . Furthermore, a possible nucleation mechanism of Li2 O2 products with different morphologies on HPCS and IrCo@HPCS electrodes was also proposed and discussed.